An analysis of the factors affecting diffusion of ICTs amongst SMEs in the hardware retail industry: a multiple case study - Chiwakira, Donald (Midlands State University, 2017)
This research was conducted for the purpose of identifying the foremost factors affecting ICT diffusion amongst small to medium-sized hardware retailers. Having embraced and implemented ICTs, SMEs operating in the hardware retailing industry stand to benefit in various ways. However, it appears that there is a significantly low rate of ICT uptake and diffusion amongst hardware retailers in Gweru. The study therefore sought to reveal the factors affecting diffusion of icts amongst small hardware retailers. The diverse influences driving these firms to adopt or repel ICTs were identified and explained. A census of all hardware retailers in the central business district of Gweru was used as the target population. This population was composed of owner-managers and employees of hardware retailing stores; a total of 16 firms, contributing a total of 65 respondents were involved. Self-administered questionnaires and follow-up interviews were used to collect this data, which was then presented and analysed using descriptive statistics. The study found that the most powerful factors that influence ICT diffusion are the affordability, compatibility and ease of use of the technologies in question. It was concluded that ICT packages that satisfied these three needs were more likely to be received and quickly spread right across organizations more readily than those which did not. Further research was recommended at a national level as this particular study was geographically limited to the city of Gweru. Similar studies in other industries can also be equally eye-opening.